Broadcasting real time information using mobile and internet technology (badminton tournament live score system) - Sughan Nair, Prabhakaran (2013)
Badminton is an international sport which is included in international games like Asian Games and Olympic Games. International badminton governing organization is known as Badminton World Federation (BWF). After the two centuries since it is founded, badminton is now widely claimed as the second most popular sport in the world behind soccer in terms of participation. Badminton is the main sport that Malaysia targets for its first Olympic gold medal. Almost all Malaysians have interest on badminton. If the game is promoted properly in Malaysia, we can produce a new generation who are committed towards this sport and become a fan and supporters for Malaysia. To develop the interest toward this sport, a platform which functions as a mediator between the fans and the sports events is needed. The need of user to know about the results of badminton tournament is fulfilled by the system. Moreover, the system enables the results reach users through email alerts and SMS messages. Besides that, it creates medium for sharing through its discussion board feature. This feature helps users to point out their thoughts and opinions about badminton sport in a good way. This webbased application is a bridge for the users to the badminton world.